Conceptualisation and Measurement of Information Needs: A Literature Review*. Issue 2 (3rd April 2017) - Afzal, Waseem
Abstract: Information need is one of the core concepts in library and information science, yet the concept is still not well understood. Nor is there clear agreement on how information needs should be measured. Understanding this concept is crucial for a discipline like library and information science, which is highly focused on meeting users' information needs. This review of the literature highlights the lack of clarity in conceptualising information need. It also explores the measurement of information need. Literature pertaining to terminological debates, contextualisation of information needs, theoretical frameworks, research methods, survey instruments and longitudinal reviews of the research on information needs informs this review. The evaluation of selected literature shows that there are terminological issues associated with defining information need; lack of theoretical foundations underpinning empirical research; and use of weak proxies, such as information seeking behaviour and information use, in the measurement of information need.